Synaptic competition sculpts the development of GABAergic axo-dendritic but not perisomatic synapses. - Elena Frola; Annarita Patrizi; Thomas Goetz; Lucian Medrihan; Enrica Maria Petrini; Andrea Barberis; Peer Wulff; William Wisden; Marco Sassoè-Pognetto (PLoS ONE)
The neurotransmitter GABA regulates many aspects of inhibitory synapse development. We tested the hypothesis that GABAA receptors (GABAARs) work together with the synaptic adhesion molecule neuroligin 2 (NL2) to regulate synapse formation in different subcellular compartments. We investigated mice ("γ2 knockdown mice") with an engineered allele of the GABAAR γ2 subunit gene which produced a mosaic expression of synaptic GABAARs in neighboring neurons, causing a strong imbalance in synaptic inhibition. Deletion of the γ2 subunit did not abolish synapse formation or the targeting of NL2 to distinct types of perisomatic and axo-dendritic contacts. Thus synaptic localization of NL2 does not require synaptic GABAARs. However, loss of the γ2 subunit caused a selective decrease in the number of axo-dendritic synapses on cerebellar Purkinje cells and cortical pyramidal neurons, whereas perisomatic synapses were not significantly affected. Notably, γ2-positive cells had increased axo-dendritic innervation compared with both γ2-negative and wild-type counterparts. Moreover heterologous synapses on spines, that are found after total deletion of GABAARs from all Purkinje cells, were rare in cerebella of γ2 knockdown mice. These findings reveal a selective role of γ2 subunit-containing GABAARs in regulating synapse development in distinct subcellular compartments, and support the hypothesis that the refinement of axo-dendritic synapses is regulated by activity-dependent competition between neighboring neurons.